EUROPEANISATION AND THE WELFARE STATE IN LITHUANIA: INSTITUTIONAL INTERSECTIONS - GUDŽINSKAS, LIUTAURAS (Politologija, 2015)
This article seeks to evaluate general trends of development of Lithuanian welfare state after the entry to the European Union (EU). Although welfare policies (social security, education, health care, family policy) are foremost implemented at national level, the EU membership certainly affects their content and direction. After Lithuania entered the EU, new opportunities to restructure its welfare policies have opened. One could seek for better governance and bigger transparency in these areas. Those opportunities have been positively induced by economic growth, exchange of public policy ideas under the method of open coordination. Also, increasing political stability should have allowed politicians to pay more attention to the welfare state and to its reforms. The article seeks to evaluate how Lithuania has so far succeeded to use these opportunities. In this regard, the concept of ‘social investment’ (as the core principle of the EU social model) is being applied. Also, one observes to what extent patronage-based governance has still been characteristic to these policies. It is shown in the analysis that these opportunities for re-structuring have not been fully utilised. Indeed, the development of Lithuanian welfare state after the entry to the EU could be described as ‘drifting’. Despite the fact that financial conditions have notably improved, the welfare state evolves inertly. Although the principle of universality has been formally retained, due to the issues of effectiveness and transparency its real implementation has been partially formal. Reflecting Soviet times, the system is still too centralised and oriented to the tertiary level of service provision. Meanwhile, those welfare policy areas where social investments could bring the biggest return, are rather neglected. Such institutional inertia is to be explained historically. Due to the lack of necessary reforms at the outset of the post-communist transformation the patronage-based governance structures have been retained or recreated. Although Lithuanian membership in the EU allowed to correct these trends, political focus on mainly questions of economic security and competitiveness does not allow to convey necessary political will for systemic reform of this area. Text consists of three parts. In the first part the main concepts of the research are presented. Also, interrelations between post-communist transformation and Europeanisation are revealed. Taking into account that the political attention at the highest level is essential for any overhaul reform of welfare state, in the second part one attempts to evaluate the changes of public discourse since the access to the EU. For this purpose, annual government reports by the Prime Minister in front of the Parliament will be taken as the primary material. Finally, in the third part one will evaluate how Lithuania responds to the current trends at the EU level to exploit welfare policies as ‘social investments’. Research is based under the logic of asymmetric comparison. In other words, one concentrates on the Lithuanian case against the broader theoretical and comparative background. Among the primary sources used in this research one should mention the poll survey of representatives of the top Lithuanian political elite conducted by the research group headed by prof. Irmina Matonytė. The research (as well as the survey) has been financed by the project “Lithuania in the EU: transformation or imitation?”, which is funded by the Lithuanian Research Council.